Synthesis and photovoltaic properties of conjugated polymers with an asymmetric 4-(2-ethylhexyloxy)-8-(2-ethylhexylthio)benzo[1, 2-b:4, 5-b′]dithiophene unit. (April 2015) - Huang, Yuanshuai; Wu, Fen; Zhang, Min; Mei, Suli; Shen, Ping; Tan, Songting
Abstract: Two novel copolymers containing an asymmetric 4-(2-ethylhexyloxy)-8-(2-ethylhexylthio)benzo[1, 2- b :4, 5- b ′]dithiophene and different conjugated side groups were designed and synthesized for polymer solar cell applications. The thermal, optical, and electrochemical properties were investigated by thermal gravimetric analysis, UV–Vis absorption, and cyclic voltammetry, respectively. The two copolymers showed a good thermal stability and solubility in common organic solvents, and relatively deep highest occupied molecular orbital (HOMO) energy levels with the values of −5.56 eV for 5, 6-difluoro-benzodiathiazole-based copolymer and −5.48 eV for isoindigo-based copolymer. The polymer photovoltaic devices based on 5, 6-difluoro-benzodiathiazole-based polymer/phenyl-C71 -butyric acid methyl ester exhibited a high open circuit voltage ( V oc ) of 0.92 V and the power conversion efficiency of 5.0%. Graphical abstract: Highlights: A novel asymmetric SBDT unit was synthesized for the first time. Two new copolymers, PSBDT–FBT and PSBDT–TID, were synthesized and applied in polymer solar cell. PSCs based on the copolymer showed a high V oc of 0.92 V and a PCE of 5.0%.